Phytoextraction of DDT‐Contaminated Soil at Point Pelee National Park, Leamington, ON, Using Cucurbita pepo Cultivar Howden and Native Grass Species. Issue 4 (1st July 2015) - Paul, Surmita; Rutter, Allison; Zeeb, Barbara A.
Abstract : A field investigation was conducted at three dichlorodiphenyltrichloroethane (DDT)‐contaminated areas in Point Pelee National Park (PPNP), Leamington, ON. Cucurbita pepo cultivar Howden and three native grass species, Schizachyrium scoparium (Michx.) Nash (little bluestem), Panicum virgatum L. (switchgrass), and Sporobolus cryptandrus (Torr.) A. Gray (sand dropseed) were grown at three different sites in the PPNP having low (291 ng/g), moderate (5083 ng/g), and high (10, 192 ng/g) soil DDT contamination levels. A threshold soil DDT concentration was identified at ∼5000 ng/g where the DDT uptake into C. pepo was maximized, resulting in plant shoot and root DDT concentrations of 16, 600 and 45, 000 ng/g, respectively. Two native grass species ( P. virgatum and S. scoparium ) were identified as potential phytoextractors, with higher shoot extraction capabilities than that of the known phytoextractor C. pepo when optimal planting density was taken into account.